Long-term stability of several endocrine disruptors in the first morning urine samples and their associations with lifestyle characteristics - Jia, Lu-Lu; Luan, Yu-Ling; Shen, Hui-Min; Guo, Ying (The Science of the total environment, 2022)
Parabens, triclosan (TCS), bisphenols, benzophenones, and phthalates are typical endocrine disruptors (EDs) with short half-lives in the human body. The concentration levels of those EDs in a spot urine sample are frequently used in exposure assessment studies, and the reproducibility of urinary levels of these nonpersistent EDs should be considered. In the present study, we consecutively collected 45-day first morning void (FMV) urine samples, as well as daily questionnaires, in six recruited participants and measured the urinary concentrations of six parabens, TCS, nine bisphenols, five benzophenones, and ten phthalate metabolites by using high-performance liquid chromatography-tandem mass spectrometry. MeP, EtP, PrP, TCS, BPA, BPS, BPF, and most phthalate metabolites were frequently detected (over 62 % of samples). The intraclass correlation coefficients (ICCs) for ED concentrations in FMV urine samples ranged from fair to excellent for MeP (0.683), EtP (0.702), BPA (0.505), BPS (0.908), BPF (0.887), BP-3 (0.712), mMP (0.661), mEP (0.523), mBP (0.500), miBP (0.724), mBzP (0.961) and all metabolites of DEHP (0.867–0.957), whereas they were low for PrP (0.321) and TCS (0.306). After creatinine adjustment, the values of ICCs for most target EDs were increased with mild to significant improvement. The stability of ED concentrations was affected by daily diet (MeP, TCS, BPA, mMP, miBP, mBP and mBzP), food containers (PrP and mECPP), use of personal care products (HMWP metabolites), pharmaceuticals (EtP) and recorded activities (BPS, mEHP, mBzP, mEHHP and mEOHP), as confirmed by a general linear mixed model. Furthermore, extending the FMV sampling period improved the probability of acceptable reproducibility (ICCs > 0.40) of MeP, EtP, BP-3 and mEP concentrations. For BPS, BPF and HMWP metabolite concentrations showed high probabilities (>80 %) of acceptable reproducibility in the last three days, and the increasing sample size slowly improved the ability to discriminate the subjects. The results were exactly the opposite for BPA concentrations. [Display omitted] •Stability of several endocrine disruptor (ED) levels in minoring urine was checked over 45 days.•The reproducibility of most EDs in 45 consecutive days was moderate to good.•Life behaviors of participants will affect the stability of ED concentration.•Measuring EDs in spot urine has >50 % chance to reflect their exposure in the last three days.